Design and analysis of circuit technique of inverter converter for induction heating (Modern Problems of Metallurgy, 2022)
For a research laboratory, the versatility and flexibility of equipment is usually one of the most important criteria. For these reasons, the task was to develop and manufacture a prototype of a laboratory inverter, capable to drive powerfull laboratory devices, like an induction heather, magnetic stress device, and so on. Among the required power leved, the wide frequency operationg range and durability are the inavoidable requirements. The article describes the schematics and design of a laboratory inverter designed for induction heating and melting. The inverter can be easily integrated into the equipment of laboratory installations (for example, intended to melt of metal in a vacuum post). It can also be used autonomously to harden and melt small samples of metals and alloys, including the color metals. The inverter power inverter is adjustable from 0 to 2 kWt, the operating frequency range from 50 kHz to 200 kHz, power supply from 220 V. A half-bridge topology was chosen as the core of the inverter construction. Was developed an undervoltage protection unit, overheat protection, a control circuit on a separate board, a voltage generator were assembled, and water cooling to the copper tubes of the oscillatory circuit was assembled. To test the efficiency of the inverter and the possibility of its operation on the load in the form of a circuit of the induction heater through the pump transformer, a series of experiments on metal heating was performed. To achieve this resuls, metal sample was placed inside the inductor coil, and the frequency was lowered from 200 kHz to 140 kHz. The power consumption from the network reached 1.5 kW. During these tests, no essentail overheating of the electornic componets was detected. The inverter has proved its efficiency during numerios tests. Due to the protection against overcurrent, overheating, low supply voltage in the control circuit, it is well suited for laboratory research on melting and heating of metal. The usage of modern element base, together with circuit solutions, allowed us to achieve the necessary parameters in terms of efficiency, operating frequency range and power.